Narrowing the Black-White Gap in Child Literacy in 1910: The Roles of School Inputs and Family Inputs - Fishback, Price V.; Baskin, John H. (The Review of Economics and Statistics, 1991)
Price V. Fishback, John H. Baskin, Narrowing the Black-White Gap in Child Literacy in 1910: The Roles of School Inputs and Family Inputs, The Review of Economics and Statistics, Vol. 73, No. 4 (Nov., 1991), pp. 725-728